Anisian (middle triassic) buildups of the Northern Dolomites (Italy): the recovery of reef communities after the permian/triassic crisis - Senowbari-Daryan, Baba; Zühlke, Rainer; Bechstädt, Thilo; Flügel, Erik (Facies, 1993)
After the end-Permian crisis and a global ‘reef gap’ in the early Triassic, reefs appeared again during the early Middle Triassic. Records of Anisian reefs are rare in the Tethys as well as in non-Tethyan regions. Most Anisian reefs are known from the western part of the Tethys but there are only very few studies focused on biota, facies types and the paleogeographical situation of these reefs. From the eastern part of the Tethys, Anisian reefs, reefal buildups or potential reef-building organisms have been reported from different regions of southern China. Most of the Anisian reefs known from western and central Europe as well as from southern China seem to be of middle and late Pelsonian age.
Gesehen am 21.02.2023